IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN INOVASI KURIKULUM PADA KURIKULUM MERDEKA DI SEKOLAH MENENGAH ATAS NEGERI 1 BATANG GANSAL KABUPATEN INDRAGIRI HULU - Yudistira, Yudistira; Musa; Alfian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of differentiated learning in enhancing curriculum innovation within the framework of the Merdeka Curriculum at SMAN 1 Batang Gansal, Indragiri Hulu Regency. The research employed a descriptive qualitative approach using purposive sampling techniques, with data collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that teachers’ understanding as designers, facilitators, and motivators is developed through self-directed learning and professional development programs facilitated by the school, although variations exist due to differences in training and competencies. The implementation of differentiated learning aligns with Tomlinson’s theory, encompassing diagnostic assessment, curriculum analysis, and implementation in aspects of content, process, product, and learning environment. This strategy plays a vital role in fostering curriculum innovation, enhancing teachers’ creativity through project-based learning and the use of interactive digital media, and positively influencing students’ motivation and engagement. Challenges in implementation occur at three levels: (1) managerial high administrative workload and limited facilities; (2) teacher lack of understanding, time constraints, and inadequate resources; and (3) student heavy learning load and low motivation. The proposed solutions include continuous teacher training, development of practical learning modules, utilization of technology through a Learning Management System (LMS), and infrastructure support funded by the School Operational Assistance Program (BOSP).